Diabetes mellitus in patients with cirrhosis: clinical implications and management. (4th April 2016) - Elkrief, Laure; Rautou, Pierre‐Emmanuel; Sarin, Shiv; Valla, Dominique; Paradis, Valérie; Moreau, Richard
Abstract: Disorders of glucose metabolism, namely glucose intolerance and diabetes, are frequent in patients with chronic liver diseases. In patients with cirrhosis, diabetes can be either a classical type 2 diabetes mellitus or the so‐called hepatogenous diabetes, i.e . a consequence of liver insufficiency and portal hypertension. This review article provides an overview of the possible pathophysiological mechanisms explaining diabetes in patients with cirrhosis. Cirrhosis is associated with portosystemic shunts as well as reduced hepatic mass, which can both impair insulin clearance by the liver, contributing to peripheral insulin resistance through insulin receptors down‐regulation. Moreover, cirrhosis is associated with increased levels of advanced‐glycation‐end products and hypoxia‐inducible‐factors, which may play a role in the development of diabetes. This review also focuses on the clinical implications of diabetes in patients with cirrhosis. First, diabetes is an independent factor for poor prognosis in patients with cirrhosis. Specifically, diabetes is associated with the occurrence of major complications of cirrhosis, including ascites and renal dysfunction, hepatic encephalopathy and bacterial infections. Diabetes is also associated with an increased risk of hepatocellular carcinoma in patients with chronic liver diseases. Last, the management of patients with concurrent diabetes and liver disease is also addressed. Recent findings suggest a beneficial impact of metformin in patients with chronic liver diseases. Insulin is often required in patients with advanced cirrhosis. However, the favourable impact of controlling diabetes in patients with cirrhosis has not been demonstrated yet.